COVID‐19: Impact of obesity and diabetes on disease severity - Al‐Sabah, Salman (Clin Obes, 2020)
The coronavirus disease 2019 (COVID‐19) pandemic is straining the healthcare system, particularly for patients with severe outcomes requiring admittance to the intensive care unit (ICU). This study investigated the potential associations of obesity and diabetes with COVID‐19 severe outcomes, assessed as ICU admittance. Medical history, demographic and patient characteristics of a retrospective cohort (1158 patients) hospitalized with COVID‐19 were analysed at a single centre in Kuwait. Univariate and multivariate analyses were performed to explore the associations between different variables and ICU admittance. Of 1158 hospitalized patients, 271 had diabetes, 236 had hypertension and 104 required admittance into the ICU. From patients with available measurements, 157 had body mass index (BMI) ≥25 kg/m(2). Univariate analysis showed that overweight, obesity class I and morbid obesity were associated with ICU admittance. Patients with diabetes were more likely to be admitted to the ICU. Two models for multivariate regression analysis assessed either BMI or diabetes on ICU outcomes. In the BMI model, class I and morbid obesities were associated with ICU admittance. In the diabetes model, diabetes was associated with increased ICU admittance, whereas hypertension had a protective effect on ICU admittance. In our cohort, overweight, obesity and diabetes in patients with COVID‐19 were associated with ICU admittance, increasing the risk of poor outcomes.